Physics education research: the teaching and learning of quantum mechanics - Lai, Joel Weijia (2017)
Undergraduate students, in their first formal encounter with Quantum Mechanics, are introduced to the shocking concepts of the quantum world. A large part of introductory quantum mechanics builds on physical theory and the corresponding mathematical formalism from Linear Algebra and Differential Equations. Students need to have a good appreciation of the physics and equipped with the relevant mathematical skills. Thus, when physics concepts are taught, students need to have been equipped with the relevant skills in mathematics in their long-term and working memory so that they are not distracted by learning the mathematics while, at the same time, learning the physics. This thesis seeks to confirm the hypothesis that the focus on mathematics distracts students from interpreting the physical picture of a quantum mechanical question. It also explores the possibility that certain personality types are more ready to learn the subject such as quantum mechanics. In response to the collected data and analysis, strategies in introducing mathematics in quantum physics are proposed and creating visuals to enhance learning and retention by stimulating working memory for different personality groups.